Simultaneous sequestration of Cr(VI) and Cr(III) from aqueous solutions by activated carbon and ion-imprinted polymers - Lesaoana, Mahadi (My University, 2018)
Macadamia activated carbon (MAC) was impregnated with different concentrations of nitric acid and heated under reflux to improve the structural characteristics of the adsorbent for both considerable reduction and enhanced removal of Cr(VI). The chemical oxidation of ACs increased the surface oxygenated functional groups. Adsorption of Cr(VI) was carried out by varying parameters such as contact time, pH, concentration, and adsorbent dosage. The optimum operating conditions for the adsorption of Cr(VI) were pH 1, contact time 240 min, adsorbent dosage 10.67 g/L and Cr(VI) concentration 100 mg/L. The results showed that the Macadamia–based AC could be used efficiently for the treatment of chromium-containing solutions as a low-cost alternative compared to commercial AC and other adsorbent reported. The results showed that treated MAC performed better than untreated MAC, signifying the effect of secondary treatment on the enhanced removal of pollutants. Comparable to the application of ACs is the development of imprinting technologies for selective metal ion remediation in environmental samples. The combination of ion imprinting effects and functionalized carbon adsorbents produce materials which effectively remove and selectively recognize the target analyte. Macadamia activated carbon (MAC) was chemically pre-treated with nitric acid to generate carboxyl groups on the surface. The carboxylated MAC was then reacted with triethylenetetramine, N,N’-diisopropylcarbodiimide and CrCl3.6H2O to produce MACN20-imprinted sorbents (MACN20-IIP). MACN20-non imprinted (MACN20-NIP) counterparts were prepared, but Cr3+ was excluded in the synthesis. Alteration of surface structural characteristics and characterization of prepared adsorbents as confirmed by Fourier transform infrared spectroscopy, thermogravimetric analysis, elemental analysis, Brunauer–Emmett–Teller and scanning electron microscopy. MACN20-IIP and MACN20-NIP adsorbents were evaluated for their Cr3+ uptake from aqueous solution in batch format. Maximum conditions were achieved at pH 5, 50 mg/L Cr(III) initial concentration and 33.33 g/L of adsorbent dosage. Presence of co-ions slightly diminished the removal of Cr(III) by MAC-IIP adsorbents. Application of the MACN20-IIP and MACN20-NIP on spiked acid mine drainage artificial sample led to collapse in the removal efficiency of MACN20-NIP while MACN20-IIP still showed good removal efficiencies. These results demonstrated that surface imprinting led to better adsorption rates and capacity. The data was better described by the Freundlich multilayer adsorption and pseudo-second order kinetic rate model. The combination of both the carbon sorbent and the surface-mediated IIPs effectively improved total chromium remediation in aqueous systems.
M. Tech (Department of Chemistry, Faculty of Applied and Computer Sciences) Vaal University of Technology.
Keywords: Simultaneous sequestration of Cr(VI), Macadamia activated carbon (MAC), chemical oxidation; Carbon sequestration.; Polymers.; Water chemistry.